A Paratextual Approach to Disney's New Mulan in China: Localization and Reception. - Shen, Chunli; Yu, Jinquan (Critical Arts: A South-North Journal of Cultural & Media Studies, 2025)
This article examines both industry-created and viewer-created paratexts of Disney's new Mulan (2020) to shed light on the localization of industry-created paratexts for Chinese audiences, the reception of the film, and the tensions between industry-created and viewer-created paratexts in China. It reveals that Disney has localized the poster, trailers and promos of Mulan for Chinese audiences by highlighting the film's all-star cast and creating an illusion of its faithfulness to The Ballad of Mulan, and the extolled virtues of filial piety and patriotism cherished in Chinese culture. The viewer-created paratext, danmu, of Mulan challenges the industry-created paratexts and demonstrates unfavorable reception of the film in China. It criticizes the film for its inauthenticity to The Ballad of Mulan, cultural appropriation, promotion of American values to meet the needs of English-speaking audiences for exoticness and cultural otherness. By investigating danmu as a viewer-created paratext, the present study has enriched paratextual research and reception studies in translation, media and film studies in the digital age.